Novos Registros sobre Meloidogyne mayaguensis no Brasil e Estudo Morfológico Comparativo com M. incognita - de Almeida, Eduardo J.; Soares, Pedro L.M.; da Silva, Adriana R.; dos Santos, Jaime M. (My University, 2008)
Almeida, E.J., P.L.M. Soares, A.R. Silva & J.M. Santos. 2008. New records on Meloidogyne mayaguensis in Brazil and comparative study with M. incognita. Meloidogyne mayaguensis is the plant-parasitic nematode responsible for a great impact on guava production in Brazil, since it has been the cause for eradication of thousand of hectares of guava plantations in the Northeastern region. In the present study, this species was detected in soybean fields of Ituverava municipality, São Paulo state, and in different vegetable crops (lettuce, cucumber, pepper and cherry tomato) in Chapada dos Guimaraes municipality, Mato Grosso state, causing root galls and other symptoms. The species was identified on the basis of the perineal pattern of females, and on the morphology and morphometry of anterior region of males. Isozyme phenotype for esterase was used for confirmation. This constitutes the first report on the occurrence of M. mayaguensis on lettuce, cucumber, pepper and cherry tomato cultures in Mato Grosso state and the first one in soybean in São Paulo state. It was found that morphological features of male anterior region and female perineal pattern are enough for the safe distinction between M. mayaguensis and M. incognita.
New records on Meloidogyne mayaguensis in Brazil and comparative study with M. incognita